(untitled) (Sebha University Conference Proceedings, 2025)
The Trombe Wall is a venerated passive-solar architectural feature, and it is a key integral to an energy-efficient construction design that functions on a friendly environmental energy source, which is solar energy. This study contemplates and delves into the convoluted interplay between air gap widths within Trombe walls and their influence on room temperature modulation and air dynamics. A comparison of diverse air gap widths of 13mm, 25mm, 34mm, 50mm, and 80mm is conducted, and an investigation of the heat transfer mechanisms and convective flow behavior is performed by utilizing computational fluid dynamics (CFD) simulations. The results illuminate optimal air gap dimensions and equip architects and engineers with imperative understandings for enhancing Trombe walls and passive heating and cooling systems in sustainable building projects.